Molecular Comparison of Free -Living Amoeba Isolated From Iraqi, Iranian and Turkish Waters - Karyagdi, Turkan K.; Mohammed, Shihab A.; Hassan, Husain F. (Iraqi Journal of Science, 2020)
Amoebas live freely in different climates and parts of the world. Several species of Free Living Amoeba (FLA) are capable of causing serious as well as fatal infections in human beings. The aim of this study was to identify and compare genotypes of water-polluting FLA in major rivers and lakes of Iraq and compare them with FLA isolates from Iran and Turkey. For this purpose, the study included 20 water samples from the Tigris River, Euphrates River , Najaf Sea and Dukan lake in Iraq, 20 water samples from Marivan, Velasht, and Soleimanshah lakes and Caspian sea in Iran, and 20 water samples from Sabanca, Seyfi , Hazar and Yay lakes in Turkey. The samples were studied by culture methods, invert microscope, and molecular methods. After inoculation and microscopic examination, cysts and trophozoites were detected in 18 cultured specimens. Overall, out of 60 water samples, 30 cases (30%) were found to be contiminated in the three countries. The highest pollution was in Turkish waters (40%), while the rate in the Iraqi and Iranian water samples was the same (25%). Because of the various species of FLA , it may be difficult to distinguish pathogenic from non-pathogenic species by culture on non-nutrient agar. Therefore, the molecular technology was applied in this study. Only a specific band of Acanthamoeba Rns genes which ranged from 423 to 551 nucleotides was observed. The isolates belonged to the T3 genotype . In addition, it was a new isolate that differs from what exists in other neighboring countries , registered in the GenBank under accession number MN462973 as the Acanthamoeba genotype T3 isolate T3 Iraq . This is the first study to detect pathogenic FLA in Iraq by PCR and Sequencing techniques. Given the high prevalence of Acanthamoeba potential pathogenic genotypes in various environmental sources and the evidence of T3 genotype in Iraqi specimens , more studies about Acanthamoeba and other pathogenic FLA for various environmental sources in Iraq are required.